La organización barrial en la dotación de los servicios básicos en el barrio de Los Ceibos cantón Machala 2013 - Bustamante Sánchez, Francis (2015)
The research work presented in this document, called "THE NEIGHBORHOOD ORGANIZATION IN THE CREW OF BASIC SERVICES IN THE NEIGHBORHOOD THE CANTON MACHALA CEIBOS 2013" presents an analysis of neighborhood organizations of the urban area of Machala; analyzing this, the legal status of organizations such as the percentage of organizations with legal existence and the proportion of neighborhood directives are legally settled in the MIES. Well studied factors such as: The participation of the inhabitants, the support for neighborhood organizations from government organizations such as MIES or Municipality and unity among members of organizations. The above related to the degree of neighborhood needs met, such as utilities and neighborhood infrastructure that have neighborhoods, sample deficiency neighborhood organizations to meet their objective, which is to seek social development for sector.